Analisa Pengaruh Variasi Elektroda dan Kuat Arus terhadap Sifat Mekanik dan Struktur Mikro Sambungan Las SMAW Baja ST 60 - yasinta, syaukaty; Wibowo, Trio Nur; Saputro, Risza Dwi Wahyu (Creative Research in Engineering (CERIE), 2025)
Abstract Welding is a metal-joining technique that involves melting a portion of the base and filler metals, with or without pressure, to produce a continuous joint. Among various welding methods, Shielded Metal Arc Welding (SMAW) is widely used in industrial applications due to its simplicity, portability, and adaptability in field conditions. This study investigates the influence of electrode type and welding current on the tensile strength and microstructure of weld joints made from low-carbon ST60 steel. The SMAW process was applied to ST60 steel plates using three types of electrodes—AWS E7013, E7016, and E7018—with welding currents of 90 A, 100 A, and 110 A. Following the welding process, tensile testing and microstructural analysis were conducted to evaluate how these parameters affected the mechanical properties and microstructural characteristics of the welds. The results indicated that the combination of the E7018 electrode and a welding current of 90 A produced the highest tensile strength, reaching 370.5 MPa. Other combinations yielded lower values: for E7013, the tensile strengths were 312.7 MPa (90 A), 335.9 MPa (100 A), and 306.5 MPa (110 A); for E7016, they were 318.7 MPa (90 A), 339.9 MPa (100 A), and 346.8 MPa (110 A); and for E7018, they were 369.5 MPa (100 A) and 350.2 MPa (110 A). Microstructural analysis revealed that the weld joint produced using the E7018 electrode at 90 A was predominantly composed of ferrite and pearlite phases, which are known for their combined ductility and hardness. These phases significantly enhance the mechanical strength of the weld joint. In conclusion, both electrode type and welding current have a substantial impact on the tensile strength and microstructural development of SMAW-welded ST60 steel joints. The most favorable outcomes in terms of mechanical performance and microstructural stability were achieved using the E7018 electrode with a welding current of 90 Keywords: ST60 steel, Shielded Metal Arc Welding (SMAW), E7013/E7016/E7018 electrodes, tensile strength, microstructure